THE CORRELATION BETWEEN WATCHING MOVIE WITH SUBTITLES AND STUDENTS’ VOCABULARY MASTERY AT UNIVERSITAS BINA DARMA - Islamia, Annisa Nur; Rosmaidar, Rosmaidar (Jurnal Ilmiah Bina Bahasa, 2020)
The aim of the research was to find out the correlation between watching movies with subtitles and students’ vocabulary mastery as well as to find out students’ perspectives that affect watching movies with subtitles and vocabulary mastery at Universitas Bina Darma. A quantitative method was used in this research. The instruments of the research were the vocabulary test and questionnaire. The samples were 60 students of the Information System Study Program Universitas Bina Darma. The samples were chosen by using the purposive sampling technique. The data were analyzed manually by using Product Moment Formula and recalculated by using Product Moment Formula from SPSS 20 Version (Statistical Package for Social Sciences). The result of the analysis showed that there was a positive medium correlation between watching movies with subtitles and students’ vocabulary mastery.